Answer:
(x+4)(x-4)(x+4i)(x-4i) (answer D)
Step-by-step explanation:
We can re-write the original binomial as a difference of squares noticing that
and that ![x^4=(x^2)^2](https://tex.z-dn.net/?f=x%5E4%3D%28x%5E2%29%5E2)
Then we have:
![x^4-256=(x^2)^2-16^2](https://tex.z-dn.net/?f=x%5E4-256%3D%28x%5E2%29%5E2-16%5E2)
Then we can factor this out using the difference of squares factor form:
![(x^2)^2-16^2=(x^2+16)(x^2-16)](https://tex.z-dn.net/?f=%28x%5E2%29%5E2-16%5E2%3D%28x%5E2%2B16%29%28x%5E2-16%29)
Now,
, is itself a difference of squares which we can factor out further:![x^2-16=x^2-4^2=(x+4)(x-4)](https://tex.z-dn.net/?f=x%5E2-16%3Dx%5E2-4%5E2%3D%28x%2B4%29%28x-4%29)
And we can also solve for the binomial:
:
![x^2+16=0\\x^2=-16\\x=+/-\sqrt{-16} \\x=+/-i\,\sqrt{16} \\x=+/-4\,i](https://tex.z-dn.net/?f=x%5E2%2B16%3D0%5C%5Cx%5E2%3D-16%5C%5Cx%3D%2B%2F-%5Csqrt%7B-16%7D%20%5C%5Cx%3D%2B%2F-i%5C%2C%5Csqrt%7B16%7D%20%5C%5Cx%3D%2B%2F-4%5C%2Ci)
then we can write ![(x^2+16)=(x+4i)(x-4i)](https://tex.z-dn.net/?f=%28x%5E2%2B16%29%3D%28x%2B4i%29%28x-4i%29)
Therefore, the final factor form of the original binomial is the product of all factors we found: ![(x+4)(x-4)(x+4i)(x-4i)](https://tex.z-dn.net/?f=%28x%2B4%29%28x-4%29%28x%2B4i%29%28x-4i%29)